STRATEGI PEMEBERDAYAAN MAHASISWA STKIP PESISIR SELATAN DALAM MEMBENTUK KARAKTER - Alexander Syam; Muhammad Arif (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
This study aims to find out and obtain information about the application of the consept of geography learning models that will form students' disaster alert characters in STKIP Pesisir Selatan by conducting meta-plan analysis and bayes analysis. This Study is descriptive qualitative using observation, interviews, and documentation in data collection. The type of data used is primary data and secondary data. Based on the results of the analysis and discussion that has been done before, it can be concluded that the Student Empowerment Strategy of South Coast STKIP In Forming Disaster Alert Character. The results of the analysis using the Bayes method there are four policy priorities that can be applied for development are 1) Students form a disaster alert group or forum with a value of 4,545 2) related socialization to disaster disaster by lecturer staff with a value of 4,524 3) emergency response training for disaster preparedness with value of 4,333 4) making direction directions to tsunami shelters and evacuation routes in several locations with a value of 4,222